EXPLORING CHALLENGES ENCOUNTERED BY NOVICE FEMALE TEACHERS REGARDING CLASSROOM MANAGEMENT IN SECONDARY SCHOOLS - Saltiel Khololo Collen Matabogei (CV. RADJA PUBLIKA, 2024)
The authors' purpose through this conceptual paper is to explore the challenges novice female teachers encounter in classroom management within secondary schools. The main question guiding this research is: